Réponses

2014-04-09T13:57:44+02:00
A= 4 tiers - 3 tiers sur 7 sixièmes - 12 sixièmes.
= 1 tiers sur moins 5 sixièmes
=1 tiers * moins 6 cinquièmes
=moins 2 cinquièmes  
Meilleure réponse !
2014-04-09T14:22:01+02:00
1)
A=4/3-1*3/3/7/6-2*6/6
A=4/3-3/3/7/6-12/6
A=-1/3/-5/6
A=-1/3*6/-5
A=-6/-15=6/15=3*2/3*5=2/5

B=2/3+1/2/17/9-1/3
B=2*2/3*2+1*3/2*3/17/9-1*3/3*3
B=4/6+3/6/17/9-3/9
B=7/6/14/9
B=7/6*9/14
B=7*9/6*14=7*3*3/3*2*14
B=21/28

2)
A=-3/4+1/2/2/5-5/2
A=-3/4+1*2/2*2/2*2/5*2-5*5/2*5
A=-3/4+2/4/4/10-25/10
A=-1/4/-21/10
A=-1/4*10/-21
A=-10/-84=5/42
-
B=1-1/3+1/4/1+1/3-1/4
B=1*12/12-1*4/3*4+1*3/4*3/1*12/12+1*4/3*4-1*3/4*3
B=12/12-4/12+3/12/12/12+4/12-3/12
B=11/12/13/12
B=11/12*12/13
B=11*12/12*13
B=11/13